Physiology of reproduction in height - the height Spermatogenesis - Monge M., Carlos (1942)
The authors studies the fertility of cats and rabbits brought to high altitudes (4000 mts.), and describe the histologic changes observed in the testicles of these animals. They noticed an inhibition of spermatogenesis, though not in every animal. Regarding cats, they state the following: 1) the cells of the seminiferous tubules, are replaced by Sertolii Syncitium, the rest being a mass of thick and granular protoplasm; 2) there are no spermatogoniae; 3) there is an increase of Leidig cells as in the resting period of certain animals which exhibit periodical spermatogenesis. Among rabbits, there is also an inhibition of spermatogenesis, but not in all individuals. Only the phase of spermatogoniae has reached. Among the germinal cells, a great number of nucleus of Sertolii Syncitium, is noticeable. All these phenomena disappear when the animal is acclimated as the authors have repeatedly testified in definite degree of inhibition followed by complete recovery.